Kegiatan Komunitas Dan Bimbingan Untuk Mendukung Kehidupan Lansia - Ramadhan Lubis; Naila Sa’adah; Via Ivanka Br Sitepu; Dalila Sari Nasution; Nadya Azmi Lianka; Nadia Ivanka (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This article explores how various community activities and forms of guidance can contribute to enhancing the overall well-being of older adults. Social engagement—ranging from regular meetups and skill-based classes to peer support groups—creates a meaningful space for seniors to remain active, connected, and valued within their communities. Participation in these activities helps support both physical and emotional health, while also fostering confidence and independence in daily life. Furthermore, consistent and well-structured guidance plays a significant role in helping older adults navigate the challenges that often accompany aging, such as emotional adjustments, health-related concerns, and changes in social relationships. Support from families, caregivers, and community networks serves as an essential foundation that enables seniors to live with greater comfort, purpose, and stability. These findings highlight the importance of integrating community involvement with supportive guidance to promote a more holistic and fulfilling life for older adults.